Ossifying Spindled and Epithelioid Tumor: A Novel Soft Tissue Tumor - Gross, John M; Zou, Ying S; Michal, Michael; Agaimy, Abbas; Garcia, Roberto A; Hysell, Christopher; Fritchie, Karen J; Dermawan, Josephine K; Rubin, Brian P; Klausner, Melanie; Morsberger, Laura; Dudley, Jonathan; et al. (Modern pathology, 2025)
This investigation describes the clinicoradiologic, pathologic, and molecular features of a unique soft tissue tumor characterized by a peripheral shell of bone and composed of bland myoid spindle and epithelioid cells that are keratin-positive. Our study cohort consists of 6 men and 6 women, with a mean age of 32 years. The tumors arose in the extremities (n = 9) and proximal limb girdle (n = 3) and were equally distributed between deep and superficial soft tissues. Patients reported dull painless masses of several months to >10 years duration (mean: 2.9 years). Imaging demonstrated a complete or partial peripheral shell of bone that could extend centrally, and the tumor's mean size was 5.7 cm. Histologically, the tumors were composed of uniform, eosinophilic myoid spindled cells growing in sheets and intersecting fascicles, surrounded by mature lamellar and/or woven bone. Also present was an admixed component of intermediate-sized epithelioid cells with eosinophilic cytoplasm. Mitotic activity was consistently low. Immunohistochemistry showed strong multifocal staining for keratins, and 50% (5/10) showed focal staining for S100; however, all were negative for SMA, desmin, SOX10, ERG, and CD34. Genetic analysis by multiple targeted RNA sequencing panels was negative (n = 10); however, whole transcriptome sequencing (n = 8) revealed a recurrent and novel in-frame SRSF7::NFATC3 fusion in 4 tumors. Dual fluorescence in situ hybridization probes for SRSF7::NFATC3 successfully confirmed this fusion and identified a fifth case, which had not undergone whole transcriptome sequencing but was negative by a targeted RNA fusion panel. Methylation profiling (n = 8) demonstrated a shared epigenetic profile distinct from other entities. Clinical follow-up (n = 11) showed no evidence of recurrence after primary excision with a mean of 41.6 months. In summary, we describe a novel soft tissue tumor designated "ossifying spindled and epithelioid tumor" as a descriptive histologic term that also emphasizes its close radiologic mimic, ossifying fibromyxoid tumor. All cases have behaved in a benign fashion without recurrence following simple excision. Awareness of this entity is important, so that it can be distinguished from other neoplasms that have more aggressive biological potential.
Keywords: radiology; SRSF7::NFATC3; ossifying spindled and epithelioid tumor; soft tissue tumor; ossifying fibromyxoid tumor; myositis ossificans